172: The Impact of a Breastfeeding Support Intervention on Breastfeeding Duration in Jaundiced Infants Admitted to a Tertiary Care Centre Hospital: A Randomized Controlled Trial. Issue 6 (1st June 2014) - Pound, C; Moreau, K; Rohde, K; Farion, K; Barrowman, N; Aglipay, M; Plint, AC
Abstract: BACKGROUND: Mothers of infants admitted to hospital with jaundice are at risk of stopping breastfeeding. OBJECTIVES: We examined the impact of a breastfeeding support intervention on breastfeeding duration in infants admitted to hospital with jaundice. DESIGN/METHODS: This was a randomized controlled trial with a qualitative component. We aimed to recruit 124 participants (62 per group). Mothers of breastfeeding infants <1 month of age admitted to the Children's Hospital of Eastern Ontario (CHEO) with a diagnosis of jaundice between October 2010 to 2013 were randomly assigned to the intervention or control group. Mothers in the intervention group met with an International Board-certified Lactation Consultant in hospital, and one to three times after discharge. Both groups received hospital standard of care for jaundice treatment. The main outcome measure was exclusive breastfeeding at three months of age. Secondary outcomes included partial and exclusive breastfeeding at various time points, number of re-hospitalizations, number of physician encounters, and number of mothers seeking breastfeeding help, all in the first six months of life. Semi-structured interviews elicited feedback on participant experiences. RESULTS: A total of 99 participants were recruited (49 in the control and 50 in the intervention group). 86 were included in the analysis of the primary outcome. There was no difference in exclusive breastfeeding at three months between groups (RR 0.77 [95% CI 0.51 to 1.14]; P=0.20) or in any of the secondary outcomes. Thirty-one participants (13 in the control group, 18 in the intervention) were included in the qualitative analysis. Intervention group participants reported an increase in comfort and confidence levels with breastfeeding, an enhanced emotional wellbeing, and a feeling of empowerment to pursue breastfeeding. Control group participants reported limited breastfeeding support in hospital, which was largely restricted to verbal information. Recommendations from both groups included the presence of an on-site lactation consultant at CHEO. CONCLUSIONS: Although the quantitative analysis failed to demonstrate significant differences between groups, feedback on the study intervention obtained in the qualitative analysis was positive. Qualitative analysis suggests an increase in mothers' confidence, which has been linked to breastfeeding duration. Further larger studies are needed to elucidate the impact of an inhospital lactation support program on successful breastfeeding.